1996
DOI: 10.1557/s1092578300002167
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cubic Phase in Epitaxial Layers of Predominantly Hexagonal GaN

Abstract: Epitaxial layers of GaN on c-plane sapphire are analyzed by continuous-wave and time-resolved photoluminescence at 4K and by X-ray diffraction. Besides the well-known emissions from hexagonal GaN we observe luminescence bands at 3.279 and 3.15 to 3.21 eV which are identified as the transition of the donor bound exciton and the donor-acceptor pair recombination in cubic GaN, respectively. Measurements of the luminescence decay times are essential for the clarification of the emission processes. Due to the probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…(These observations are supported by TEM measurements on similar films by Xin et al (1996) which indicate a relatively high proportion of the cubic phase close to the layer-substrate interface.) In the hexagonal phase the DBE transition occurs 32 meV below the band edge-if we assume a similar exciton binding energy in cubic material, we obtain a cubic band gap in close agreement with the 3.302 eV measured by Ramirez-Flores et al It is important, in this context, that almost all the published PL data includes reference to an emission line close to 3.27 eV, which is almost certainly excitonic in origin as indicated by the very short decay time (Klann et al 1995, Strauss et al 1997a, while Hwang et al (1994) also reported seeing both hexagonal and cubic lines from the same sample, separated by 204 meV and showing closely similar pressure coefficients. This seems strong evidence for the cubic band gap being approximately 200 meV smaller than that of hexagonal material, as we claimed earlier.…”
Section: Cubic Gansupporting
confidence: 89%
See 2 more Smart Citations
“…(These observations are supported by TEM measurements on similar films by Xin et al (1996) which indicate a relatively high proportion of the cubic phase close to the layer-substrate interface.) In the hexagonal phase the DBE transition occurs 32 meV below the band edge-if we assume a similar exciton binding energy in cubic material, we obtain a cubic band gap in close agreement with the 3.302 eV measured by Ramirez-Flores et al It is important, in this context, that almost all the published PL data includes reference to an emission line close to 3.27 eV, which is almost certainly excitonic in origin as indicated by the very short decay time (Klann et al 1995, Strauss et al 1997a, while Hwang et al (1994) also reported seeing both hexagonal and cubic lines from the same sample, separated by 204 meV and showing closely similar pressure coefficients. This seems strong evidence for the cubic band gap being approximately 200 meV smaller than that of hexagonal material, as we claimed earlier.…”
Section: Cubic Gansupporting
confidence: 89%
“…Straightforward analysis of this model yields a value of E A 80 meV. Somewhat similar results have been reported by Strauss et al (1996) for cubic GaN as we discuss below. In summary, we can only wait for confirmation of these speculations but the weight of evidence must favour an effective valence band mass of about 0.7 m-the evidence of exciton binding energy appears too strong to be denied.…”
Section: Electronic Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…A multiexponential decay is observed as expected for this transition. 15 The lifetime of the DAP 1 is between 5 and 20 ns. The LO replica of the DAP band is indicated by arrows.…”
mentioning
confidence: 99%
“…This line corresponds to radiative recombination of excitons bound at neutral donor (nitrogen vacancy) [9]. The two lines at 3.43 and 3.37 eV are related to oxygen impurity [10] and to a defect of unknown nature [11], respectively. An additional line related to the thick layer of In x Ga 1−x N is observed in the spectral range from 2.85 eV to 3.25 eV.…”
Section: Bulk Layers Of In X Ga 1−x N and Ganmentioning
confidence: 99%